Non-contrast mDixon MR angiography of the neck: Comparison with time-of-flight MR angiography in normal subjects - Mizoshiri, Tomohiro; Yoshida, Morikatsu; Oda, Seitaro; Tsumagari, Shota; Nakaura, Takeshi; Harada, Kazunori; Ikeda, Osamu (Medicine (Baltimore), 2021)
We investigated the feasibility of non-contrast three-dimensional modified Dixon (mDixon) magnetic resonance angiography (MRA) to evaluate the carotid artery.We studied 30 normal patients who underwent non-contrast mDixon and conventional time-of-flight (TOF) MRA of the neck with a clinical 3T MR scanner. Carotid artery signal-to-noise ratio (SNR) and contrast-to-noise ratio were compared between mDixon-MRA and TOF-MRA. Two readers independently evaluated vessel sharpness, image contrast, and overall image quality using a 4-point scale.SNR was significantly higher on mDixon-MRA than TOF-MRA (P < .01). There was no significant difference in contrast-to-noise ratio. The visual score for vessel sharpness was significantly higher on mDixon-MRA than TOF-MRA (P < .01), whereas the score for contrast was significantly higher on TOF-MRA (P < .01).Although non-contrast three-dimensional mDixon-MRA showed lower visual contrast than conventional TOF-MRA, it provided images with significantly higher SNR and better vessel sharpness than TOF-MRA.